Oxford international Lower secondary English student book 2 for grade 7 - Danihel, Emma (Karachi : Oxford university press, 2023)
"Oxford International Lower Secondary English Student Book 2" is a comprehensive English textbook designed for Grade 7 students following an international curriculum. The book focuses on developing key English language skills, including reading, writing, listening, speaking, and grammar, through engaging and interactive content.
Keywords: English : Textbook